2015
DOI: 10.1111/1745-5871.12150
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring to Learn, Learning to Monitor: A Critical Analysis of Opportunities for Indigenous Community‐Based Monitoring of Environmental Change in Australian Rangelands

Abstract: Indigenous community‐based monitoring has been a central feature in many international attempts to improve monitoring of and local adaptation to environmental change. Despite offering much promise, Indigenous community‐based monitoring has been underutilised in natural resource management in Australia, particularly within the remote, semi‐arid rangelands. This paper discusses contextual social and environmental factors that may help to explain this apparent deficiency, before critically analysing key stakehold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 67 publications
(122 reference statements)
0
13
0
Order By: Relevance
“…The higher number of articles describing collaborative monitoring could be explained by the broader trend of engaging Indigenous communities in research and monitoring practices, whereas externally-driven monitoring is likely influenced by conventional, government or researcher implemented monitoring approaches [110], as well as requests by Indigenous communities for external monitoring support [53,94]. However, successful CBM generally occurs when communities monitor things they personally connect with and care about, rather than for externally-driven needs [111,112]. Moreover, in the context of climate research, studies initiated with and by Indigenous community members tend to indicate more responsible community engagement than studies initiative by outside researchers alone [113].…”
Section: Externally Driven Monitoringmentioning
confidence: 99%
“…The higher number of articles describing collaborative monitoring could be explained by the broader trend of engaging Indigenous communities in research and monitoring practices, whereas externally-driven monitoring is likely influenced by conventional, government or researcher implemented monitoring approaches [110], as well as requests by Indigenous communities for external monitoring support [53,94]. However, successful CBM generally occurs when communities monitor things they personally connect with and care about, rather than for externally-driven needs [111,112]. Moreover, in the context of climate research, studies initiated with and by Indigenous community members tend to indicate more responsible community engagement than studies initiative by outside researchers alone [113].…”
Section: Externally Driven Monitoringmentioning
confidence: 99%
“…It is, therefore, useful to also consider the use of other approaches to obtain water level data. Citizen science is now more frequently used to obtain environmental data over large areas (Savan et al, 2003;Bonney et al, 2009;Graham et al, 2011;Fohringer et al, 2015;Huddart et al, 2016;Wiseman and Bardsley, 2016). Little et al (2016) gave citizen scientists water level sounders to measure groundwater levels in private wells and found that these measurements provided valuable data on groundwater levels across a large area in Alberta, Canada, and that the measurements were relatively accurate; the root mean square error between citizen scientist observed water levels and pressure transducer based water levels ranged between 3 and 11 cm.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, useful to also consider the use of other approaches to obtain water level data. Citizen science is now more frequently used to obtain environmental data over large areas (Bonney et al, 2009;Fohringer et al, 2015;Graham et al, 2011;Huddart et al, 2016;Savan et al, 2003;Wiseman and Bardsley, 2016). Little et al (2016) gave citizen scientists water level sounders to measure groundwater levels in private wells and found that these measurements provided valuable data on groundwater levels across a large area in Alberta, Canada, and that the measurements were relatively accurate; the root mean square error between citizen scientist observed water levels and pressure transducer based water levels ranged between 3 and 11 cm.…”
mentioning
confidence: 99%